Time series of δ26Mg variability in precipitation of north‐west Germany. (9th November 2021) - Riechelmann, Sylvia; Spötl, Christoph; Immenhauser, Adrian
Abstract: This study presents δ 26 Mg values, Mg 2+ concentrations, δ 18 O and δ 2 H values of monthly collected rain and snow samples between 2014 and 2017 from north‐west Germany. The δ 26 Mg values of snow are similar to those of rain. Unlike δ 18 O and δ 2 H, neither δ 26 Mgprecipitation values nor Mg 2+ concentrations display a relationship with air temperature. In contrast, δ 26 Mgprecipitation values and Mg 2+ concentrations are correlated with precipitation amount. As previously suggested by other studies but now based on a larger data set, it is proposed that the δ 26 Mg values and Mg 2+ concentrations are affected by the mineralogical composition and amount of airborne dust. Consequently, a small number of random precipitation samples cannot represent the complex processes influencing the δ 26 Mgprecipitation values. δ 26 Mgprecipitation can be used to differentiate between seawater aerosols, carbonate and silicate dust. Silicate dust is typified by higher Mg concentrations and δ 26 Mg values compared to carbonate dust. Concerning carbonates, dolostone dust has higher Mg concentrations and δ 26 Mg values, while limestone dust is Mg‐lean with lower δ 26 Mg values. Dust of anthropogenic origin in the region can come from active limestone and dolostone quarries, surface mining of siliciclastics, and agriculture on silicate‐rich soils. Although dust of this mineralogy can also be of natural origin, most natural dust consists of airborne silicates transported by wind systems from the Sahara to Europe. Higher δ 26 Mgprecipitation values would indicate silicate or dolostone dust influx. Lower δ 26 Mgprecipitation values suggest lower dust concentrations and a predominantly calcitic dust mineralogy. It appears that δ 26 Mgprecipitation is most probably influenced by changes in weather conditions and natural and anthropogenic dust origin. This study implies that δ 26 Mgprecipitation is a potential proxy for dust mineralogy and fluxes. Nevertheless, further research should include the determination of atmospheric dust mineralogy and their fractions as well as air mass back trajectory analysis to identify the source(s) of dust. Abstract : This study presents Mg isotope values of monthly collected rain and snow samples between 2014 and 2017 from north‐west Germany. Magnesium isotope signatures of rain and snow show a high variability and are not influenced by air temperature. Influencing factors on the Mg isotope composition of rain and snow are (I) precipitation amount, and (ii) mineralogy of natural and anthropogenic dust.